Higher modified dietary inflammatory index is associated with increased risk of osteoporosis in US adults: Data from NHANES - Chen, Yong; Chen, Fu-hua; Chen, Yi-qing; Zhang, Qiu (Frontiers in Nutrition, 2022)
Objectives: To study the relationship between modified dietary inflammatory index (MDII) score with osteoporosis (OP) in adult Americans. Methods: Data were extracted from the United States National Health and Nutrition Examination Survey (NHANES) (2007-2008, 2009-2010, 2013-2014, and 2017-2018). In this cross-sectional study, 5,446 participants were included and analyzed. Potential dietary inflammatory was assessed by MDII score (24-hour recall), a composite method computed according to the relationship between nutrients and systemic pro-inflammatory cytokine level, and was further classified into tertiles. Weighted multivariable logistic regression analysis was employed to examine the associations between osteoporosis and MDII score. Results: In weighted multivariable-adjusted logistic regression models, the highest tertile of MDII score was associated with an increased risk of osteoporosis (OR:1.73, 95CI%:1.14-2.63). In participants aged over 59, higher MDII score showed a higher risk of osteoporosis (OR:1.92; 95CI%:1.16-3.15). In the sex-stratified models, the results remained significant only among women (OR: 1.80; 95%CI: 1.02-3.17). In the menopausal status stratified model, after adjusting potential confounding variables, the association between the MDII score, either as a categorical (OR: 1.88; 95%CI: 1.07-3.13) or continuous variables (OR: 1.19; 95%CI: 1.02-1.38), and osteoporosis risk was significant among post-menopausal women. Conclusions our study indicates that a higher MDII score (pro-inflammatory effect) is significantly associated with an increased risk of osteoporosis in US adults, especially among those post-menopausal women more than 60 years. This study further supports those dietary changes have the potential to prevent OP.